Mempelajari Sifat Fisik Kerupuk Berbahan Tepung Melinjo Dan Tepung Gaplek - Alda Monica Febrianty; Tamrin Tamrin; Sapto Kuncoro; Warji Warji (abe.fp.unila.ac.id, 2023)
The taste of crackers can be varied by mixing two or more raw materials. Crackers can be made from a mixture of melinjo flour and cassava (gaplek) flour. The purpose of this study is to know and indentify the physical characteristics of crackers made from a mixture of melinjo flour and geplek flour.This study used a completely randomized design (CRD) with 6 different treatments, these are the mixture of melinjo flour and gaplek flour P1(100%, 0%), P2 (80%, 20%), P3 (60%, 40%), P4 ( 40%,60%), (20%,80%), P6(0%,100%). This study uses several parameters to be measured such a hardness, density, color, taste, and crispness. The result of this study showed that the hardness of each treatment is relatively the same. The density of crackers showed that the higher the melinjo flour content, the higher the density. There was a change in the color of the crackers before and after they were fried. The results showed that the concentration of 20% melinjo flour and 80% cassava flour were the most preferred types of crackers by the panelists. Keywords: Crackers, Gaplek, Melinjo, Physical Characteristics And Mixture